The COVID-19 Pandemic's Effects on Voter Turnout - Matteo Picchio; Raffaella Santolini (Institute of Labor Economics (IZA), 2021)
The COVID-19 pandemic has increased the risk of participating in public events, among them elections. We assess whether the voter turnout in the 2020 local government elections in Italy was affected by the COVID-19 pandemic. We do so by exploiting the variation among municipalities in the intensity of the COVID-19 outbreak as measured by the mortality rate among the elderly. We find that a 1 percentage point increase in the elderly mortality rate decreased the voter turnout by 0.5 percentage points, with no gender differences in the behavioural response. The effect was especially strong in densely populated municipalities. We do not detect statistically significant heterogeneous effects between the North and the South or among different levels of autonomy from the central government.
Keywords: D72; D81; H70; 330; COVID-19; outbreak; pandemic; voter turnout; mortality rate; Italian municipalities